The differential interaction of Brucella and ochrobactrum with innate immunity reveals traits related to the evolution of stealthy pathogens. - Elías Barquero-Calvo; Raquel Conde-Alvarez; Carlos Chacón-Díaz; Lucía Quesada-Lobo; Anna Martirosyan; Caterina Guzmán-Verri; Maite Iriarte; Mateja Mancek-Keber; Roman Jerala; Jean Pierre Gorvel; Ignacio Moriyón; Edgardo Moreno; et al. (PLoS ONE, 2009)
BACKGROUND:During evolution, innate immunity has been tuned to recognize pathogen-associated molecular patterns. However, some alpha-Proteobacteria are stealthy intracellular pathogens not readily detected by this system. Brucella members follow this strategy and are highly virulent, but other Brucellaceae like Ochrobactrum are rhizosphere inhabitants and only opportunistic pathogens. To gain insight into the emergence of the stealthy strategy, we compared these two phylogenetically close but biologically divergent bacteria. METHODOLOGY/PRINCIPAL FINDINGS:In contrast to Brucella abortus, Ochrobactrum anthropi did not replicate within professional and non-professional phagocytes and, whereas neutrophils had a limited action on B. abortus, they were essential to control O. anthropi infections. O. anthropi triggered proinflammatory responses markedly lower than Salmonella enterica but higher than B. abortus. In macrophages and dendritic cells, the corresponding lipopolysaccharides reproduced these grades of activation, and binding of O. anthropi lipopolysaccharide to the TLR4 co-receptor MD-2 and NF-kappaB induction laid between those of B. abortus and enteric bacteria lipopolysaccharides. These differences correlate with reported variations in lipopolysaccharide core sugars, sensitivity to bactericidal peptides and outer membrane permeability. CONCLUSIONS/SIGNIFICANCE:The results suggest that Brucellaceae ancestors carried molecules not readily recognized by innate immunity, so that non-drastic variations led to the emergence of stealthy intracellular parasites. They also suggest that some critical envelope properties, like selective permeability, are profoundly altered upon modification of pathogen-associated molecular patterns, and that this represents a further adaptation to the host. It is proposed that this adaptive trend is relevant in other intracellular alpha-Proteobacteria like Bartonella, Rickettsia, Anaplasma, Ehrlichia and Wolbachia.